Способи, порядок та форма перерозподілу спадщини як механізму забезпечення прав спадкоємців - Кухарєв, О. Є.; Kukharev, O. Y.; ORCID: http://orcid.org/0000-0003-2086-9179 (Право і суспільство. - 2023. - № 1. - С. 77-84, 2023)
З’ясовано способи, порядок та форми перерозподілу спадщини, а також їх співвідношення за цивільним законодавством України з урахуванням положень правової доктрини та матеріалів судової практики. Наголошено, що перерозподіл спадщини – це повторний розподіл спадщини між спадкоємцями у тому випадку, коли після первісного її розподілу в натурі спадщина була прийнята іншими спадкоємцями. Первісний розподіл спадщини пов’язаний з її оформленням, що завершується отриманням спадкоємцями свідоцтв про право на спадщину. Законом сформульовано імперативний перелік способів перерозподілу спадщини: передання частини спадкового майна у натурі; сплата грошової компенсації. Застосування певного способу перерозподілу спадщини залежить від наявності чи відсутності у спадкоємців спадкового майна в натурі. Заперечено віднесення до способів перерозподілу спадщини направленої відмови від прийняття спадщини, визнання договору недійсним, а також визнання права власності на спадкове майно.

The article is focused on clarifying the methods, procedure and form of inheritance redistribution, as well as their correlation under the civil legislation of Ukraine taking into account the provisions of legal doctrine and caselaw materials. It has been emphasized that inheritance redistribution is duplicative distribution of inheritance among the lawful heirs in case if inheritance was accepted by other heirs after its initial distribution in kind. The initial inheritance distribution is related to its registration, which ends with receiving certificates of heirship by the lawful heirs. The law has formulated imperative list of methods of inheritance redistribution: transfer of a part of inherited property in kind; payment of monetary compensation. The application of a certain method of inheritance redistribution depends on the presence or absence of inherited property in kind among lawful heirs. The author of the article rejects the attribution of intended refusal to accept the inheritance, the invalidity of the contract, as well as the recognition of the right of ownership of inherited property to the methods of inheritance redistribution. The conclusion has been substantiated that arising relations at the same time of inheritance redistribution based on the applications of the lawful heirs are not contractual in nature. Inheritance redistribution by the court is carried out by using a special method of protecting the rights of lawful heirs – by making changes into the certificate of heirship. At the same time, such independent methods of protecting the rights of lawful heirs as making changes into the certificate of heirship and declaring such a certificate invalid, should be singled out on the basis of the grounds and legal consequences. Declaring the certificate of heirship invalid cannot be considered as inheritance redistribution by its nature. The form of inheritance redistribution is the issuance of new certificate of heirship, which is carried out by a notary on the basis of applications submitted by the lawful heirs or a court decision that has entered into force.

Установлены способы, порядок и формы перераспределения наследства, а также их соотношение по гражданскому законодательству Украины с учетом положений правовой доктрины и материалов судебной практики. Подчеркнуто, что перераспределение наследства – это повторное распределение наследства между наследниками в том случае, когда после первоначального его распределения в натуре наследство было принято другими наследниками.
Methods, Procedure and Form of Inheritance Redistribution as the Mechanism for Ensuring the Rights of Lawful Heirs
Кухарєв, О. Є. Способи, порядок та форма перерозподілу спадщини як механізму забезпечення прав спадкоємців / Кухарєв О. Є. // Право і суспільство. - 2023. - № 1. - С. 77-84. - DOI: https://doi.org/10.32842/2078-3736/2023.1.11.
Keywords: Цивільне право. Civil Law. Гражданское право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Спадкове право. Inheritance law. Наследственное право; спадкування; inheritance; наследование; спадкові правовідносини; hereditary legal relations; наследственное правоотношение; спадкоємець; inheritor; наследник; спадщина; heritage; наследство; розподіл спадщини; distribution of inheritance; распределение наследства; перерозподіл спадщини; redistribution of inheritance; перераспределение наследства; свідоцтво про право на спадщину; certificate of right to heritage; свидетельство о праве на наследство